2015
DOI: 10.1371/journal.pone.0117093
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Natural Selection at the FTO (Fat Mass and Obesity Associated) Locus in Human Populations

Abstract: Background and aimsPolymorphisms in the first intron of FTO have been robustly replicated for associations with obesity. In the Sorbs, a Slavic population resident in Germany, the strongest effect on body mass index (BMI) was found for a variant in the third intron of FTO (rs17818902). Since this may indicate population specific effects of FTO variants, we initiated studies testing FTO for signatures of selection in vertebrate species and human populations.MethodsFirst, we analyzed the coding region of 35 vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…The ultimate goal of the work was to elucidate and underscore rapid population-specific fixation of the obesity associated genetic variant (haplotype) in European populations based on FTO intron 1 expanded haplotype frequency profiling in the major continental supergroups of the1000 Genome Project. We also observed quite rapid evolutionary rate of the locus displayed by European populations, implying that a selective sweep might have taken place in its evolutionary course [25]. Our conclusions corroborate the BMI WHO report summed up in [21], which contrasted obesity risks in East Asian vs European populations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The ultimate goal of the work was to elucidate and underscore rapid population-specific fixation of the obesity associated genetic variant (haplotype) in European populations based on FTO intron 1 expanded haplotype frequency profiling in the major continental supergroups of the1000 Genome Project. We also observed quite rapid evolutionary rate of the locus displayed by European populations, implying that a selective sweep might have taken place in its evolutionary course [25]. Our conclusions corroborate the BMI WHO report summed up in [21], which contrasted obesity risks in East Asian vs European populations.…”
Section: Discussionsupporting
confidence: 87%
“…It was corresponded recently that the FTO gene in human has experienced natural selection pressure in the course of evolution [ 25 ], possibly featuring population adaptation to the climatic environment, from the hot climate areas to the cold sustaining regions [ 26 ]. A range of studies underlined its involvement in thermogenesis [ 10 ] and cell metabolism [ 27 ] and it was reported that FTO affects the obesity trait in age- dependent manner [ 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vladimir Babenko and colleagues [ 24 ] analyzed the FTO gene locus for its haplotype profiles within eighteen 1000G populations from 4 continental groups. Their study points that this obesity-associated locus evolved rapidly, confirming previously reported evidence of the selective sweep [ 25 ], which took place in the transcription factors binding sites-enriched sequences within intron 3 of FTO .…”
supporting
confidence: 82%
“…At the molecular level, some data suggest that selection pressures may have acted on obesity-related loci in FTO (60). 'Thrifty variants' in CREBRF in Samoans (61) and variants in LCT are strongly associated with BMI (62,63).…”
Section: In Pursuit Of Thriftmentioning
confidence: 99%
“…Because FTO contributes to obesity , is associated with phenotypic variability of BMI and is also highly sensitive to environmental factors such as diet and physical activity , FTO may regulate variation in body type as per Feinberg and Irizarry's model . Comparing genomes of humans and vertebrates, a recent paper demonstrates that most coding sites in FTO show signals of strong purifying selection and neutral mutation, leading Liu and colleagues to argue that FTO was historically under positive selection. Recent research, however, provides evidence against the applicability of Feinberg and Irizarry's model to obesity .…”
Section: To Be Thrifty or Not To Be Thrifty? Obesity And The Epigenomementioning
confidence: 99%